Comparison of Hospital Emergency Room Management Regulations in Indonesia Before and During The COVID-19 Pandemic: Literature Study - Luckyta Ayu Puspita Sari; Inge Dhamanti (Universitas Nusa Cendana, 2022)
The emergency room is the main gateway for the spread of viruses and diseases, both between patients and between patients and medical personnel. WHO said that in the era of the COVID-19 pandemic, the highest risk of spreading COVID-19 was in the emergency room due to the high mobility of the emergency room, but the patient's disease had not been fully detected, so that the prevention of this disease was carried out through efforts to change the management of the hospital's emergency room. This research was conducted in order to find out the efforts made by the government through a comparison was made between the policy settings for hospital emergency rooms before during the COVID-19 pandemic which included entry flows, service procedures, zone mapping, and the distribution of health human resources in hospital emergency rooms. The new regulations for hospital emergency rooms during the COVID-19 pandemic regulate facilities and infrastructure in the emergency room as well as management of health human resources that adapt to the conditions of the COVID-19 pandemic in Indonesia. The new regulation also requires health screening and the application of health protocols, supporting examinations (swab tests), and the flow of patient examinations in the emergency room which refers to the guidelines of the Ministry of Health of the Republic of Indonesia and guidelines from the CDC. The implementation of the new regulations is a form of responsive and adaptive attitude of hospitals in Indonesia to the conditions of the COVID-19 pandemic.